Evaluation of the Efficiency of Treatment with Rituximab for Systemic Scleroderma (A Case Report) - E. N. Harlamova; Ju. Ju. Karpenko (Архивъ внутренней медицины, 2021)
The article describes a clinical case of a progressive form of systemic scleroderma in a 39-year-old man. The patient has an acute course and rapid progression of the disease with a significant initial decrease in the forced vital capacity of the lungs, with signs of an unfavorable prognosis, such as a diffuse form, a high skin count (> 14), male sex, and high positivity for antibodies to Scl-70. In connection with the ineffectiveness of standard therapy with glucocorticoids and immunosuppressants at an early stage of the disease, the option of treatment with genetically engineered drugs (rituximab) was considered. As a result of the therapy, a positive trend was noted.